Analysis of cumulative live birth rate outcomes of three ovarian stimulation protocols in patients after laparoscopic cystectomy of ovarial endometrioma: a retrospective cohort study - Jiaheng Li; Yijiang Li; Mengnuo Li; Xianling Zhao; Wei Zheng; Junwei Zhang; Yuchao Zhang; Jing Li; Yichun Guan (Reproductive Health, 2023)
Abstract Background Previous studies have reported that after laparoscopic cystectomy of ovarial endometrioma, the ovarian response to gonadotropin (Gn) significantly decreased. However, for patients with diminished ovarian reserve (DOR) after ovarian surgery, how to choose the most appropriate controlled ovarian hyperstimulation protocol has not been concluded. Compared with the traditional agonist regimen, the gonadotropin (Gn)-releasing hormone (GnRH) antagonist, microstimulation, and progestin-primed ovarian stimulation (PPOS) protocols are simple to operate and have a shorter cycle, which are often used in patients with DOR. So the purpose of our study is to compare the assisted reproductive outcomes of these three controlled ovarian hyperstimulation protocols in patients with DOR following laparoscopic cystectomy of ovarial endometrioma. Methods In this retrospective cohort study, 89 patients with DOR who had undergone in vitro fertilisation/intracytoplasmic sperm injection at the Department of Reproductive Medicine at the Third Affiliated Hospital of Zhengzhou University from 1 to 2018 to 31 December 2020 were included. According to the controlled ovarian hyperstimulation protocols employed, the patients were divided into GnRH antagonist (38 patients), PPOS (27 patients), and microstimulation (24 patients) groups. The basic data and clinical outcomes of the three groups were compared. The main outcome measure was the cumulative live birth rate. Results No significant differences in the age of the female patients and their spouses and female patients’ body mass index and basal endocrine levels (follicle-stimulating hormone and oestradiol) were noted among the three groups (P > 0.05). The GnRH antagonist group had higher antral follicle counts, greater endometrial thickness on the human chorionic Gn injection day, greater number of oocytes retrieved, and higher two pronuclear embryo counts than did the other two groups. However, the starting dosage of Gn was lower in the GnRH antagonist group than in the other two groups. The microstimulation group had a significantly higher oocyte output rate and high-quality embryo rate than did the other two groups (P < 0.05). No significant differences in the total dosage of Gn, cumulative pregnancy rate, cumulative live birth rate, viable embryo rate, and blastocyst formation rate were observed among the three groups (P > 0.05). Conclusion In conclusion, for patients aged under 40 years who experienced DOR after laparoscopic cystectomy of ovarial endometrioma, GnRH antagonist protocol and PPOS protocol can obtain better ovulation induction outcomes and cumulative live birth rate than microstimulation protocol, and are more suitable ovulation induction protocols.